2014
DOI: 10.1016/j.ijgo.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of early postpartum pain and healing outcomes after mediolateral versus lateral episiotomy

Abstract: Incidence and extent of pain in the first 10 days after LE correspond to those after adequately performed MLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 25 publications
1
25
0
2
Order By: Relevance
“…activities of daily living, and amount of analgesic use. The authors found no significant differences in overall pain scores from any rating system or in the amount of analgesics used (38). These findings are in compliance with and support the observational study findings in Paper I and Paper II, comparing different episiotomy techniques and perineal pain perception the first day after delivery and at 3 months postpartum.…”
Section: Perineal Painsupporting
confidence: 82%
“…activities of daily living, and amount of analgesic use. The authors found no significant differences in overall pain scores from any rating system or in the amount of analgesics used (38). These findings are in compliance with and support the observational study findings in Paper I and Paper II, comparing different episiotomy techniques and perineal pain perception the first day after delivery and at 3 months postpartum.…”
Section: Perineal Painsupporting
confidence: 82%
“…More space also allows for instrumentation of assisted deliveries by forceps or vacuums (Cargill 2004; Murphy 2008a). At other times, episiotomy is performed to shorten second stage of labour for various maternal and fetal indications (Hamilton 1861; Hartmann 2005) such as maternal exhaustion and fetal bradycardia.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research [5,8,9], approximately 70% of the patients suffered from perineal pain due to an episiotomy at D7 postpartum. To show a relative reduction of at the least 30% in this incidence in the ropivacaine arm, with 90% power at the 5% level of signi cance, and a bilateral test, the study requires 124 women with episiotomy in each group.…”
Section: Sample Sizementioning
confidence: 99%
“…Perineal pain is a common consequence of episiotomy and affects up to 97% of women on day 1 postpartum [5,6], up to 70% of women at day 7 to 10 postpartum [7][8][9] and may persist until at least 5 months postpartum [10,11]. Pain after perineal wound (apart from episiotomy) are also reported but less studied because of the high variability of the localization and the depth of the tear.…”
Section: Introductionmentioning
confidence: 99%